Psychological health of women who have conceived using assisted reproductive technology in Taiwan: findings from a longitudinal study - Huang, Mei-Zen (BMC Womens Health, 2019)
BACKGROUND: Despite the increasing use of Assisted Reproductive Technology (ART) and the significant physical and emotional commitments that these treatments and procedures involve, only limited evidence exists regarding the psychological health of women who undergo ART. This study investigated the changes over time in the psychological health of women who have conceived using ART during the first, second, and third trimesters of pregnancy and during the postpartum period in Taiwan. METHODS: A quantitative longitudinal study was conducted at a fertility centre in Taiwan. 158 pregnant women who had conceived using ART completed a web-based questionnaire that included the following instruments: State Anxiety Inventory, Edinburgh Postnatal Depression Scale, Modified Maternal Foetal Attachment Scale, Pregnancy Stress Rating Scale, Maternity Social Support Scale, Intimate Bond Measure, and Parenting Stress Index. The data were collected the first (9–12 weeks), second (19–22 weeks), third (28–31 weeks) trimesters of pregnancy and at 7–10 weeks postpartum. RESULTS: Levels of anxiety and depression, which are both key indicators of psychological health, were highest during the first trimester, with scores of 42.30 ± 11.11 and 8.43 ± 4.44, respectively. After the first trimester, anxiety scores decreased and remained stable through the remainder of pregnancy, with scores of 38.03 ± 10.58 in the second and 38.39 ± 10.36 in the third trimester, but increased at two-months postpartum, attaining a score of 41.18 ± 11.68. Further, depression scores showed a similar pattern, declining to a mean of 7.21 ± 4.23 in the second and 6.99 ± 4.11 in the third trimester and then increasing to 8.39 ± 5.25 at two-months postpartum. Pregnancy stress and social support were found to be the most important predictors of change in psychological health during pregnancy and the postpartum period. CONCLUSION: Psychological health was found to be poorest during the first trimester and at two-months postpartum. Moreover, pregnancy stress and social support were identified as key predictors of change in psychological health. The findings indicate a need for increased sensitivity among healthcare professionals to the psychological vulnerability of women who have conceived using ART as well as a need to introduce tailored interventions to provide appropriate psychological support to these women.